CONCEPT AND STRUCTURE OF THE COMPETENCE OF TEACHERS OF THE FINE ARTS (Pedagogy of Higher and Secondary Education, 2007)
The author make an attempt to define the conception of competence offuture teachers cffine art. The typical scheme of socialindividual andprcfessional-value competences is worked out.
Keywords: competence; didactical system; fine art; means o f education